HUMAN RESOURCE MANAGEMENT IN IMPROVING QUALITY OF PUBLIC SERVICES IN SAMSAT KABANJAHE - Mukhlis Syarif; Syafruddin Ritonga; Maksum Syahri Lubis (SOSIOEDUKASI, 2026)
This study aims to analyze the role of human resource management in improving the quality of One-Stop Integrated Services (PTSP) at UPT PEPENDA (SAMSAT) Kabanjahe. The approach used is qualitative descriptive with data collection techniques through in-depth interviews, observations, documentation, and data triangulation. The focus of the research is directed at the aspects of planning and sufficiency of human resources, recruitment, training and development, work motivation, performance evaluation, and their implications for the speed, accuracy, and responsiveness of public services. The results of the study show that the implementation of PTSP has provided easy access to services for the community, but its effectiveness is highly dependent on the quality and management of human resources. The limited number of employees in a certain period still affects the waiting time for services. Continuous training, work motivation, and performance evaluation play an important role in maintaining service quality. Cross-agency synergy, especially with the National Police of the Republic of Indonesia, also strengthens the accuracy and certainty of service. This research emphasizes that strengthening human resource management is the key to improving the quality of sustainable public services.